Soil microbial networks’ complexity as a primary driver of multifunctionality in photovoltaic power plants in the northwest region of China - Zhao, Liuqing; Xu, Sumeng; Zhao, Jinmei; Chen, Shujuan; Liu, Xiaolong; Zheng, Xiuyuan; Wang, Xiuhui; Zhu, Zhao; Gao, Fei; Fu, Bingzhe; Li, Shuxia (Frontiers in Microbiology, 2025)
IntroductionExploiting photovoltaic power generation as a novel source of clean energy has become increasingly common in recent times. Nevertheless, the impact of photovoltaic power plants (PVs) on soil microbial activity and several functions is unclear.MethodsThe present investigation aims to collect soil samples from photovoltaic power plants in arid and semi-arid regions with different years of construction, determine the physicochemical properties of the soil, and employ high-throughput sequencing to obtain 16S rRNA and ITS genes from the PV. This approach examines the community composition of bacteria and fungi in plant soils. This dataset is adopted to explore the role of soil physicochemical characteristics and climatic factors in the variousness and complexness of the network of soil microbial communities in PVs.ResultsThe findings reveal that soil physicochemical properties exhibit a gradual increase over time, with bacterial and fungal diversity showing a corresponding gradual increase and reaching a maximum over a period of 5–10 years. Furthermore, it is observed that the topological properties of the microbial network underwent significant changes driven by microbial diversity. Bacterial and fungal diversity as well as network complexity also display positive and negative correlations, respectively. A positive and significant correlation is detected between the bacterial network complexity and the soil multifunctionality, whereas a substantial negative correlation is observed between the fungal network complexity and the soil multifunctionality.DiscussionIn conclusion the environment is able to directly regulate soil microbial diversity, thereby affecting network complexity and driving soil multifunctionality. Such discoveries are aimed to have crucial ecological implications for predicting environmental-soil-microbial effects on soil multifunctionality in photovoltaic zones.